2021
DOI: 10.3390/microorganisms9081774
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Invasive Pneumococcal Disease Differs between Risk Groups in Norway Following Widespread Use of the 13-Valent Pneumococcal Vaccine in Children

Abstract: The elderly and adults with medical risk conditions remain at high risk of invasive pneumococcal disease (IPD), highlighting the importance of adequate preventive efforts. In an observational population-based study in Norway (pop ≥ 5 years, 2009–2017) covering six years post-PCV13 implementation, we explored the incidence and risk of IPD associated with age and comorbidities. We obtained the data on 5535 IPD cases from the Norwegian Surveillance System for Communicable Diseases and the population data from Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…We identified that for each episode of invasive PnPn there are at least three episodes of non-invasive PnPn, which is in line with findings in other studies [5,6]. We found that the number of episodes was 8 times higher in the oldest age group (age 80+) compared to the youngest (age 50-59), indicating that the risk of hospitalisation due to non-invasive PnPn increases with age, just like IPD [8]. This corresponds to observations reported from other countries [3,16,20,21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We identified that for each episode of invasive PnPn there are at least three episodes of non-invasive PnPn, which is in line with findings in other studies [5,6]. We found that the number of episodes was 8 times higher in the oldest age group (age 80+) compared to the youngest (age 50-59), indicating that the risk of hospitalisation due to non-invasive PnPn increases with age, just like IPD [8]. This corresponds to observations reported from other countries [3,16,20,21].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with these findings, a more recent study from the Netherlands (among 409 patients) found that 30% of the PnPn episodes were invasive and 70% non-invasive [6]. Both, young children, elderly and persons with weakened immune systems are at high risk of acquiring pneumococcal disease [7, 8].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In Norway, after 2016, a declining incidence of IPD caused by both PCV13 (13-valent pneumococcal conjugate vaccine) and non-PCV13 IPD was observed, though the proportion of non-PCV13 serotypes is increasing compared to PCV13 serotypes. 4 …”
Section: Introductionmentioning
confidence: 99%